QUALITATIVE STUDY OF PERCEPTIONS ON POVERTY AND PRESENT STATUS OF ASSETS IN A MAYAN COMMUNITY IN THE YUCATAN PENINSULA - Robles-Zavala, Edgar; Fiechter-Russo, Tara (Ecosistemas y Recursos Agropecuarios, 2014)
The aim of this study is two fold. First, it explores the local discourse about poverty in a highly mar-ginalized municipality in the state of Yucatan, Mexico. Second, the study examines the present status of assets of 90 households through qualitative and quantitative techniques. The assessment was carried out using the Sustainable Livelihood Approach. The study concluded that the conditions of poverty in the households are closely linked to insti-tutional factors, rather than to economic factors. The most severe constraints observed in the homes of the community were the low productivity of the milpa system, the lack of livestock, a food deficit, low social capital, corruption and incorrect public policies. These problems may be addressed by a combination of local participatory policies focussed on the solution of the multiple factors that determine the poverty and marginalization in the community.
Keywords: Poverty perceptions; assets; mayas; humid tropics; Yucatan.